Disease‐induced and treatment‐induced alterations in body composition in locally advanced head and neck squamous cell carcinoma. Issue 1 (19th September 2019) - Willemsen, Anna C.H.; Hoeben, Ann; Lalisang, Roy I.; Van Helvoort, Ardy; Wesseling, Frederik W.R.; Hoebers, Frank; Baijens, Laura W.J.; Schols, Annemie M.W.J.
Abstract: Background: Chemoradiation or bioradiation treatment (CRT/BRT) of locally advanced head and neck squamous cell carcinoma (LAHNSCC) comes with high toxicity rates, often leading to temporary tube feeding (TF) dependency. Cachexia is a common problem in LAHNSCC. Yet changes in body composition and muscle weakness during CRT/BRT are underexplored. Strong evidence on the effect of TF on body composition during treatment is lacking. The aim of this cohort study was to assess (i) the relationship of fat‐free mass index (FFMI) and handgrip strength (HGS) with CRT/BRT toxicity and outcome, (ii) body composition in patients treated with chemoradiation (cisplatin) vs. bioradiation (cetuximab), and (iii) the effect of the current TF regime on body composition and muscle strength. Methods: Locally advanced head and neck squamous cell carcinoma patients treated with CRT/BRT between January 2013 and December 2016 were included ( n = 137). Baseline measurements of body composition (bioelectrical impedance analysis) and HGS were performed. Toxicity grades (Common Terminology Criteria for Adverse Events) were scored. In a subset of 69 patients, weight loss, body composition, and HGS were additionally assessed during and after CRT/BRT. TF was initiated according to the Dutch guidelines for malnutrition. Results: In this cohort (68% male, mean age 59 ± 8 years), the incidence of baseline muscle wasting, defined as FFMI < P10, was 29%. Muscle wasting was present in 23 of 100 (23%) chemoradiation patients and 17 of 37 (46%) bioradiation patients ( P = 0.009). Muscle‐wasted patients required more unplanned hospitalizations during CRT ( P = 0.035). In the chemoradiation subset, dose‐limiting toxicity was significantly higher in wasted vs. non‐wasted patients (57% vs. 25%, P = 0.004). Median follow‐up was 32 months. Multivariate Cox regression analysis identified muscle wasting as independent unfavourable prognostic factor for overall survival [hazard ratio 2.1 (95% CI 1.1–4.1), P = 0.022] and cisplatin as favourable prognostic factor [hazard ratio 0.3 (95% CI 0.2–0.6), P = 0.001]. Weight and HGS significantly decreased during CRT/BRT, −3.7 ± 3.5 kg ( P < 0.001) and −3.1 ± 6.0 kg ( P < 0.001), respectively. Sixty‐four per cent of the patients required TF 21 days (range 0–59) after CRT/BRT initiation. Total weight loss during CRT/BRT was significantly ( P = 0.007) higher in the total oral diet group (5.5 ± 3.7 kg) compared with the TF group (3.0 ± 3.2 kg). Loss of FFM and HGS was similar in both groups. Conclusions: In LAHNSCC patients undergoing CRT/BRT, FFMI < P10 is an unfavourable prognostic factor for overall survival, treatment toxicity, and tolerance. Patients experience significant weight and FFM loss during treatment. Current TF regime attenuates weight loss but does not overcome loss of muscle mass and function during therapy. Future interventions should consider nutritional intake and additional strategies specifically targeting metabolism, loss of muscle mass, and function.